INFORMATIVITY OF PSYCHOPATHOLOGICAL SYMPTOMS IN PATIENTS WITH CONSEQUENCES OF CRANIOCEREBRAL TRAUMAS - Волошина, Д.Н. (World of Medicine and Biology, 2014)
By means of a questionnaire of expressiveness of psychopathological symptoms Derogatіs, it is surveyed: 39 patients with others (except dementia, amnestic syndrome and delirium) the mental disorders caused CCT (the code number of diagnosis F06 for ICD-10); 61 patient with personal disorders and behavioral disorders due to CCT (the code number of diagnosis F07 for ICD-10), and also 73 practically healthy person. Data are processed by methods of mathematical statistics (the dispersive analysis). For all studied signs diagnostic quotients (DQ) and measures of informativity Kullback (MI) are calculated. Informativity and diagnostic significance of psychopathological symptoms of consequences of CCT was defined. It was created necessary preconditions for use of this symptoms in strictly formal diagnostic procedures (type of consecutive procedure Вальда), which computer realization is a basis of modern medical expert systems. It is offered to investigate informativity and the diagnostic significance of indicators: of addictive status and quality of life of patients with consequences of CCT for the purpose of working out of complex diagnostics and differential diagnostics of mental and behavioral disorders in patients of this category.
Keywords: craniocereberal traumas; psychopathological symptomatology; diagnostic significance